2019
DOI: 10.1111/tpj.14477
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin enhances cotton immunity to Verticillium wilt via manipulating lignin and gossypol biosynthesis

Abstract: SummaryPlants endure challenging environments in which they are constantly threatened by diverse pathogens. The soil‐borne fungus Verticillium dahliae is a devastating pathogen affecting many plant species including cotton, in which it significantly reduces crop yield and fiber quality. Melatonin involvement in plant immunity to pathogens has been reported, but the mechanisms of melatonin‐induced plant resistance are unclear. In this study, the role of melatonin in enhancing cotton resistance to V. dahliae was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 103 publications
(124 reference statements)
6
85
0
Order By: Relevance
“…Melatonin acts as a hormone in plants, and as a signaling molecule in a wide range of biological activities [5]. For example, melatonin treatment enhances plant tolerance against many stresses, including salt [6,7], drought [8,9], viruses [10], pathogens [11,12], waterlogging [13], and senescence [14], among others [15][16][17]. Melatonin is also involved in plant development processes such as growth [18,19], seed viability [20], flowering [21,22], endoplasmic reticulum (ER) quality control [23,24], secondary metabolite synthesis [25], and others [26].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin acts as a hormone in plants, and as a signaling molecule in a wide range of biological activities [5]. For example, melatonin treatment enhances plant tolerance against many stresses, including salt [6,7], drought [8,9], viruses [10], pathogens [11,12], waterlogging [13], and senescence [14], among others [15][16][17]. Melatonin is also involved in plant development processes such as growth [18,19], seed viability [20], flowering [21,22], endoplasmic reticulum (ER) quality control [23,24], secondary metabolite synthesis [25], and others [26].…”
Section: Introductionmentioning
confidence: 99%
“…Application of exogenous melatonin to cotton could induce the expression of phenylpropanoid mevalonate (MVA), gossypol and other pathway-related genes, thus leading to increased lignin and gossypol concentrations in metabolites of this pathway and thus enhancing the resistance of cotton to Verticillium wilt [76]. Liu et al [77] found that spraying of 50 mol L −1 of melatonin solution on tomato fruits can induce and enhance the activity of disease-resistant proteases CHI, GLU, PAL and PPO, and significantly enhance disease resistance to Botrytis cinerea by regulating ROS accumulation and JA defense signaling pathways.…”
Section: The Regulation Of Melatonin Resistance To Biological Stressmentioning
confidence: 99%
“…Especially the repetitively identi ed cis- the inoculation of pathogens, changes in the expression patterns of phenylpropanoid related OMT genes were identi ed. These identi ed OMT genes included GhOMT49, GhOMT58, GhOMT20, and GhOMT61 that were found signi cantly expressed in 12 and 48 hours post inoculation Verticillium dahliae (Li et al 2019a). In the current study, these genes were down-regulated under abiotic stresses and in ber development stages (Fig.…”
Section: Omts Are Involved In Diverse Cis-regulatory Elementsmentioning
confidence: 99%